2012
DOI: 10.1016/j.juro.2011.10.041
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Anogenital Distance and Reproductive Hormone Levels in Adult Men

Abstract: Anogenital distance may provide a novel metric to assess testicular function in men. Assuming that anogenital distance at birth predicts adult anogenital distance, our findings suggest a fetal origin for adult testicular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 21 publications
7
99
2
Order By: Relevance
“…Our finding that fetal deficits in androgen action can result in compromised adult Leydig cell function in rodents fits with emerging evidence from humans (14,16). There is a similar connection between reduced fetal androgens and reduced adult sperm counts/sperm production in men and rats (15,16).…”
Section: -Hsd3supporting
confidence: 87%
See 1 more Smart Citation
“…Our finding that fetal deficits in androgen action can result in compromised adult Leydig cell function in rodents fits with emerging evidence from humans (14,16). There is a similar connection between reduced fetal androgens and reduced adult sperm counts/sperm production in men and rats (15,16).…”
Section: -Hsd3supporting
confidence: 87%
“…There is also evidence from human (13,14) and animal experimental (15) studies that fetal programming can influence adult testosterone levels, particularly that reduced fetal androgen exposure leads to lower adult male testosterone levels (14,15). This data fits with growing evidence that subtle deficiency in fetal androgens is a major determinant of adult male reproductive disorders, such as low sperm production (16,17), and might explain why low sperm counts are often associated with compensated Leydig cell failure in men (18).…”
supporting
confidence: 67%
“…In humans, recent studies have reported shorter AGD in boys with hypospadias or cryptorchidism as compared with boys with normal genitalia (Hsieh et al 2008), and decreased AGD in adult men has been correlated to changes in semen parameters and decreased testosterone level (Eisenberg et al 2011, 2012a, 2012b, Mendiola et al 2011. The reproductive effects of prenatal BPA exposure in humans was evaluated by Miao et al (2011), who compared AGD in sons of workers who had or had not been occupationally exposed to BPA during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, AGD could be measured at any postnatal age in rats and used to retrospectively decipher the level of fetal androgen exposure during the MPW (11,21). In human males, AGD shows similar male-female differences as in rats (11,(24)(25)(26), and lower AGD has been related to the occurrence of TDS disorders evident at birth (27)(28)(29)(30)(31)(32)(33) and, in a majority of studies, to lower sperm counts (34)(35)(36)(37) and hormone levels (38,39) in adult men, similar to rats (reviewed in ref. 11).…”
Section: Introductionmentioning
confidence: 99%